Legal Analysis And Problems of The 2024 Simultaneous General Elections In Indonesia: Implementation Strategies And Their Implications For Democracy - Madakarah, Finradost Yufan; Wisnaeni, Fifiana (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Simultaneous general elections in 2024 in Indonesia are expected to improve the quality of democracy and public participation. However, its implementation was faced with various challenges, including problems with the implementation, participant participation, and errors in vote counting. This research aims to identify the basis of election law, explore the problems that arise, and develop effective resolution strategies. Through normative analysis and sociological juridical approaches, this study finds that the orientation of organizers, the preparation of attributes, and adequate infrastructure facilities are the keys to overcoming problems. The implications of this election include improving the quality of democracy, higher public engagement, and transparency and accountability in the electoral process. The results of this research are expected to provide insights and recommendations for election organizers and other stakeholders to create more democratic elections